Pemanfaatan Bahasa Jawa sebagai Dasar Utama Perkembangan Moral Anak pada Usia Dini oleh Masyarakat Desa Salam: Indonesia - Putri, Rosi Octharyna; Setyawan, Bagus Wahyu (Jurnal Bahasa dan Sastra, 2024)
Children's morals at an early age need to be built so that they develop properly. The moral development of children will be closely related to the habits that are formed in daily life following their growth period. Parents can start from the habit of behaving and speaking. Familiarizing children to speak politely must be the main awareness for parents. One of the foundations in efforts to build the moral development of early childhood is through Javanese krama. Javanese krama is a language that has deep character values. Through the habit of speaking Javanese krama, children will get used to respecting their interlocutors, respecting their elders, loving their peers, and even respecting themselves from an early age. However, many parents are afraid to teach their children to speak Javanese krama for difficult reasons and are afraid of being wrong. The results of this study reveal that there are strategic ways that can be done by parents in getting used to Javanese krama so that it can be realized as a foundation for the moral development of early childhood. In Salam Village, there is a strategic method through the stages of recognizing, observing, self-improvement, motivation, training from an early age, and getting used to it every day.